Fluid evolution and metallogenesis of the Zhangjiapingzi gold deposit in mianning, Sichuan province: constraints from fluid inclusion studies - Yan, Bing; Zhu, Liye; Zhang, Jiaqi; Lai, Chuan; Yan, Han; Wei, Wen Feng; Jiang, Haiyun (Frontiers in Earth Science, 2023)
The Zhangjiapingzi gold deposit, located at the western margin of the Yangtze Craton and controlled by the Jinhe-Chenghai deep fault, is a newly discovered super-large gold deposit in the Danba-Mianning metallogenic belt. The gold ore bodies are hosted in the Middle Triassic (T2) altered dolomite (Dm), and have two types of mineralization: altered rock type and quartz vein type. Previous studies on this deposit are rare, especially on the ore-fluid characteristics, which limit the understanding on the ore genesis. This study focused on fluid inclusions in quartz from altered rocks, and used microthermometry and laser Raman spectroscopy to investigate the properties and sources of oreforming fluids, and to determine the ore genetic type. The results show that the fluid inclusions are mainly CO2-H2O-NaCl inclusions, with medium temperature (220-300℃), low salinity (<10%), medium-low density (0.54-1.06 g/cm 3 ) and high contents of CO2 and CH4, resembling typical orogenic gold ore fluids. We suggest that the Zhangjiapingzi is best classified as orogenic type, and our findings provide new insights into the fluid origin and metallogenesis of orogenic gold deposits in the Danba-Mianning metallogenic belt.